2013
DOI: 10.13172/2052-0069-2-3-874
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of degradation of biodegradable medical devices

Abstract: Introduction This paper presents a set of case studies for calculating the degradation rates of medical devices made of biodegradable polymers using the finite element method. Case StudyFirstly, a set of experimental data in the literature showing size effect of the degradation was analysed; it was shown that the finite element model is able to fit the experimental data fairly well. Then four different devices were analysed to demonstrate the applications of finite element analysis in device design. These incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Consequently, the compliance between biodegradation rate and regeneration need to be controlled. 64 The sudden degradation of both types of scaffolds after 1 week can be adduced to the high capacity of interaction with water molecules. Similar studies reported that freeze-cast scaffolds maintained their stability more than the prepared constructs with other techniques when the same materials were used.…”
Section: Swelling Capacity and Biodegradation Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the compliance between biodegradation rate and regeneration need to be controlled. 64 The sudden degradation of both types of scaffolds after 1 week can be adduced to the high capacity of interaction with water molecules. Similar studies reported that freeze-cast scaffolds maintained their stability more than the prepared constructs with other techniques when the same materials were used.…”
Section: Swelling Capacity and Biodegradation Ratiomentioning
confidence: 99%
“…Based on another report, the larger pores such as resultant pores in the synthesized OCG1 samples terminated to heterogeneous biodegradation. 64 The sudden degradation of both types of scaffolds after 1 week can be adduced to the high capacity of interaction with water molecules. However, the observed steady gradient after first week may be due to lamellar-type pores and its influence on high mechanical strength.…”
Section: Swelling Capacity and Biodegradation Ratiomentioning
confidence: 99%
“…Pan and co-workers (Pan, 2014) developed a mathematical model for the degradation of bioresorbable polymers. Han and Pan (Han and Pan, 2013) presented a series of case studies of using a commercial finite element package, COMSOL Multiphysics, to obtain the molecular weight distributions in degrading implants. Here their model is used to obtain the distributions of molecular weight in the plate shown in Fig.…”
mentioning
confidence: 99%
“…1. Details of the degradation model can be found in (Pan, 2014) and (Han and Pan, 2013). Table 1 provided the model parameters which are used in the calculation for molecular weight distributions using COMSOL Multiphysics.…”
mentioning
confidence: 99%
See 1 more Smart Citation